Cardiopulmonary Exercise Testing-Guided Exercise Therapy in Hypertensive Patients: A Single Center Study - Qin Lu; Jingjing Lu; Che Li; Ping Huang; Fenfen Jiang; Xia Zhao; Jianqin Zhang; Yi Huang; Zhenliang Chu (Cardiovascular Therapeutics)
Conclusion: In addition to drug treatment, cardiac rehabilitation guided by CPET can effectively improve blood pressure control, reduce blood pressure variability, improve cardiorespiratory function and lipid metabolism, and increase exercise endurance in patients with Grade 1 hypertension. Its efficacy is clear and safe, with clinical value for promotion.